Work Fatigue, Body Mass Index, Individual Characteristics, and Their Relationships to Work Stress Among Elementary School Teachers in Semarang, Central Java, Indonesia - Ida Wahyuni; Yuliani Setyaningsih; Khairun Nisa; Rosyida Alya Nadhifa (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Work-related stress is a psychological and physiological condition that occurs when individuals are unable to cope with pressures arising from their job demands. Teachers are particularly vulnerable to stress due to multiple factors such as workload, curriculum demands, employment status, interpersonal relationships, and individual characteristics. Previous surveys in Central Java have reported that approximately 70% of teachers experience work-related stress, highlighting the urgency of this issue. This study aims to analyze the relationship between work fatigue, body mass index (BMI), gender, and age with work stress in elementary school teachers. Subjects and Method: This study used a cross-sectional design conducted in public elementary schools in Tembalang and Banyumanik Districts, Semarang, Central Java, Indonesia, in late 2025. The study population was elementary school teachers in that area, with a sample of 201 teachers taken using a purposive sampling technique. The dependent variable was work stress (measured with the GHQ-12 questionnaire). Independent variables included job fatigue (measured with the “Kuesioner Alat Ukur Perasaan Kelelahan Kerja/KAUPK2” or Work Fatigue Assessment Questionnaire in Indonesian language), BMI, gender, and age. Results: A total of 58.2% of teachers experienced high work stress. Bivariate test results showed no statistically significant relationship between job fatigue (OR=1.12; 95% CI= 0.560 to 2.321; p=0.185), BMI (OR=0.98; 95% CI=0.801 to 4.110; p=0.410), gender (OR=97; 95% CI= 0.981 to 3.105; p=0.249), and age (OR=1.01; 95% CI=0.331 to 4.102; p=0.843) with work stress. Conclusion: The studied factors such as job fatigue, BMI, gender, and age were not proven to be significantly associated with work stress in this sample. A possible policy implication is the need to focus on creating a healthy organizational work environment rather than on individual teacher characteristics.